2021
DOI: 10.3390/antibiotics10070800
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Usage in Commercial and Domestic Poultry Farming in Two Communities in the Ashanti Region of Ghana

Abstract: Poultry farming is a common practice in Ghana. Antibiotics are used, particularly in commercial poultry farming, as growth promoters and to prevent and cure infections. However, there is little information on antimicrobial usage in domestic poultry farming in Ghana. This study aimed to describe antimicrobial usage in commercial and domestic poultry farming. A cross-sectional survey was conducted within the Ashanti region of Ghana including 33 commercial farms and 130 households with domestic poultry farming. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…Similarly, a study conducted in Ghana showed that many poultry farmers consulted veterinary officers on antibiotics [61]. Consulting veterinarians is essential because they can provide expert and necessary information to the poultry farmers about the antibiotics used to treat animal diseases [55]. In the current study, the majority of the participants stated that they observed the treatmentwithdrawal period and never treated market-ready birds with antibiotics, although this was not verified.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, a study conducted in Ghana showed that many poultry farmers consulted veterinary officers on antibiotics [61]. Consulting veterinarians is essential because they can provide expert and necessary information to the poultry farmers about the antibiotics used to treat animal diseases [55]. In the current study, the majority of the participants stated that they observed the treatmentwithdrawal period and never treated market-ready birds with antibiotics, although this was not verified.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, a study in Ghana reported that commercial farmers tend to be more aware of AMR and antibiotic use than medium and small-scale farmers [54]. In low-and medium-income countries (LMICs), small-scale farmers have been reported to have limited information about AMR and are more likely to misuse antibiotics compared to medium-scale and commercial layer farmers [54,55]. This could be because commercial farmers keep more birds than medium-scale and small-scale farmers.…”
Section: Discussionmentioning
confidence: 99%
“…The high antimicrobial-resistant rate observed in our study agrees with findings from similar studies conducted in both low and middle-income countries [65] and high-income countries [66] showing an increasing trend of antibiotic resistance in Campylobacter spp. The increasing trend might also be due to the extensive use of antimicrobials in animal farming for growth promotion and prophylaxis [67] and the indiscriminate use in humans [68]. Carbapenem resistance is on the increase in Gram-negative bacteria [69]; however, our review observed that all isolates tested against imipenem were susceptible.…”
Section: Discussionmentioning
confidence: 96%
“…Antibiotics have been used for many decades in the poultry industry to enhance production, promote growth performance, and protect birds from pathogenic microbes (12)(13)(14)(15)(16). For example, supplementation of broilers' diet with antibiotics could increase body weight gain by 5.8 % (17).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are also important for fighting infectious pathologies (16,19,20) such as necrotic enteritis and coccidiosis (21). Broadly, antibiotics are used in phytosanitary treatments, feed additives, and prophylactic treatments in animals and humans.…”
Section: Introductionmentioning
confidence: 99%